P-78 Patient-reported outcome measures: how frequently are they completed by patients in hospices?. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Gibbins, Jane; Huddart, Melanie; Scott, Kirsty; Stevens, Deborah; Campbell, Carolyn
Abstract : Background: Patient-Reported Outcome Measures (PROMs) are fundamental in any care setting to determine the perspective of those receiving the care. A recent systematic review highlighted that most evidence about the use of PROMs in palliative care populations is in the outpatient oncology setting. There is little evidence about the completion of PROMs in the inpatient palliative care setting. St Christopher's Index of Patient Priorities (SKIPP) 2 is a validated questionnaire exploring symptoms and quality-of-life and given to all patients on their third and tenth day of hospice stay. The completion of one SKIPP on the third day has been used as a PROM as it enquires about the patients' symptoms and quality of life prior to, and after contact/admission to the hospice service. Methods: A retrospective analysis from 150 consecutive admissions lasting four or more days across two hospice sites in the South West of England to determine the completion rates of SKIPP. Results: Of 150 admissions, 61 stayed less than 10 days (and thus expected to complete one SKIPP) and 89 stayed longer than 10 days (and thus expected to complete two SKIPPs). One SKIPP form was completed by 57.3% of all patients. Of the patients who stayed for 10 days or greater, 33.7% completed a second SKIPP form. The most common reasons for non-completion were the patient was too unwell (44.3%), or the form was not able to be completed on day three (21.4%) and therefore deemed an inappropriate outcome measure. Discussion: Nearly 60% of patients managed to complete one SKIPP questionnaire which can be used alone as a PROM for patients in an inpatient palliative care setting. This suggests PROM can be routinely embedded into clinical practice within a hospice setting.